Regeneration of Jatropha curcas using leaf explants - Pappusamy, Arokiaraj; S.A, Lydia; L., Norshahidah; K, Latiffah (2010)
A tissue culture protocol for regeneration of Jatropha curcas using leaf explants via somatic embryogenesis was established. The best response for callus induction from leaf explants was on Murashige and Skoog (MS) medium containing BA (1.0 and 2.0 mg l-1) and IBA (1.0 mg l-1). Callus was maintained in light and dark on MS medium supplemented with 0.5 mg l-1 BA and 0.5 mg l-1 IBA. The best response for shoot induction and shoot multiplication was on treatments containing (1.0 – 2.0 mg l-1) BA. The shoots were elongated and rooted on ½ strength MS medium containing 1.0 mg l-1 NAA (Napthalene Acetic Acid).